'If Clodia despised Catullus, you can very well, Dionysus, despise Ariadne': classical receptions and Roman elegy in Hilda Hilst's Discontinuous and Remote Ode for Flute and Oboe. From Ariadne to Dionysus (1969). (4th February 2023) - Gorab Leme, Fernando
Abstract: After her depiction in Catullus 64, Ariadne became a model for the relicta, the abandoned woman. The tapestry that ornamented the wedding of Peleus and Thetis told exactly of her dismay and anger upon learning that Theseus left her. As far as the myth goes, following her abandonment, Dionysus took her as a wife. Modernist Brazilian author Hilda Hilst (1930–2004) revisits this portion of the tale in her cycle of ten poems Discontinuous and Remote Ode for Flute and Oboe. From Ariadne to Dionysus (1969). This introduces the poems as works of reception vis-à-vis the ancient figurations of Ariadne, as well as the context of Hilst's biography, it analyses them as reimaginations of the Roman elegy, and presents their first complete English translation, all original endeavours. On the surface, Hilst's Ariadne fashions herself as a learned poet who reads Catullus and rejoices in her abandonment. I argue that upon a closer look, however, this endlessly unrequited woman desires instead union and permanence. Hilst, herself an underappreciated and disreputable figure, unveils Ariadne's labyrinthic mind as she negotiates her devotion to poetry and her desire for the man she loves, revealing the afterlife of the myth of a heroine who found her own voice.